PENGARUH PEMBELAJARAN DARING TERHADAP MINAT BELAJAR SISWA PADA MATERI POKOK PANCASILA DI SD NEGERI 105329 WONOSARI - Tulus Sirait (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2022)
The problem in this research is the low learning ability of students on the subject matter of Pancasila at SD Negeri 105329 Wonosari. This research was conducted at SD Negeri 105329 Wonosari Tanjung Morawa Kab. Deli Serdang. This type of research is a quantitative research with a descriptive format. Descriptive quantitative research is a research that has the aim of increasing students' interest in learning on the subject matter of Pancasila at SD Negeri 105329 Wonosari, totaling 46 students. This study provides a pretest to determine the location of the difficulty of student interest in learning on the subject matter of Pancasila. The results of the analysis show that the influence of online learning on interest in learning is 66.2%. So that 33.8% of learning interest is influenced by factors other than online learning. Thus, it can be concluded that the influence of online learning on students' interest in learning on the subject matter of Pancasila at SD Negeri 105329 Wonosari for the 2020/2021 Academic Year Thus, it can be concluded that the influence of online learning on interest in learning and student learning outcomes on the subject matter of Pancasila at SD Negeri 105329 Wonosari in the 2020/2021 academic year has the effect of online learning